1979
DOI: 10.1111/j.1399-6576.1979.tb01486.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Analgesic Dose‐Effect Relationships of Nefopam and Oxycodone in Postoperative Pain

Abstract: The analgesic dose-effect relationship of nefopam was compared in a double-blind randomised trial with that of oxycodone in immediate postoperative pain. Nefopam 15 mg or oxycodone 4 mg was given every 10 min i.v. (maximum six times) to patients in pain after upper abdominal surgery until their wound pain (scored 0-3) disappeared. The mean pain intensity (PI), initially 2.2 in both groups, descreased by approximately the same extent for up to two doses in both groups (to 1.5 after nefopam 30 mg and to 1.1 afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
2

Year Published

1981
1981
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
1
16
2
Order By: Relevance
“…This contrasts with reports conceming the parenteral use ofthe drug where increases in pulse rate (Tigerstedt et al, 1977;Tigerstedt et al, 1979) and blood pressure (Dodson, 1980) have been observed.…”
Section: Respiratory and Metabolic Effects Of Oral Nefopam In Human Vcontrasting
confidence: 53%
See 3 more Smart Citations
“…This contrasts with reports conceming the parenteral use ofthe drug where increases in pulse rate (Tigerstedt et al, 1977;Tigerstedt et al, 1979) and blood pressure (Dodson, 1980) have been observed.…”
Section: Respiratory and Metabolic Effects Of Oral Nefopam In Human Vcontrasting
confidence: 53%
“…However increasing the dose of nefopam did not increase the severity of the respiratory depression. Clinical studies on the analgesic action of nefopam have also suggested that increasing the dose of nefopam does not necessarily increase its maximum effect (Tigerstedt et al, 1977;Tigerstedt et al, 1979). Depression of the CO2 response by nefopam suggests that it might enhance the respiratory depressant effects of other drugs, for example the narcotic analgesics.…”
Section: Respiratory and Metabolic Effects Of Oral Nefopam In Human Vmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that 10-30% of patients given a low dose of nefopam experience nausea, usually after its first administration. 25 Nefopam may affect the incidence of nausea by modulating chemical mediators such as serotonin.…”
mentioning
confidence: 99%